A critical review on nonnative English teacher identity research: from 2008 to 2017. Issue 6 (3rd July 2019) - Yuan, Rui
ABSTRACT: This paper reviews existing studies ( n = 22) on nonnative English teacher identity in L2 school contexts from 2008 to 2017. Through a systematic and rigorous process of paper selection and analysis, three major themes were identified, i.e. (1) identity development through social engagement; (2) identity conflicts and struggle at intrapersonal, interpersonal, and contextual levels; and (3) identity crisis with teacher attrition. The paper also offers a critical review on the research methodologies adopted in current nonnative teacher identity research and points out directions for future research. Based on the findings, the paper proposes a tentative framework on NNESTs' identity trajectory and calls for a transformative and action-oriented approach that can explore effective ways to promote identity development for NNESTs and teachers of different linguistic, subject and sociocultural backgrounds.